Rancang Bangun Sistem Pemonitor Gelombang Otak Nirkabel Berbasis Mikrokontroler - Budi Bayu Murti (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2021)
Humans are a very complex living system composed of billions of active cells working together to form tissues. The neural network that is awakened has an information transmission system based on the body's electricity or bioelectricity. All surfaces of the human skin and body parts have electrical properties and impedance that can be detected to indicate health conditions. In the biomedical field the measurement of bioelectric signals becomes one of the important aspects. Bioelectric measurements to monitor heart conditions are known as ECG (Electrocardiography), EMG (muscle electromyography), ENG (nerve electroneurography). Signals from the brain are detected from electroenchepalography (EEG) signal parameters. The study was developed by a sensor system capable of noninvasive brain waves and and capable of sending signals wirelessly through RF radio waves in real-time. The device is built using a TGAM sensor, a microcontroller interface, Bluetooth device, and the LabView application. Tests were carried out to measure the range and frequency range of the EEG. The object of measurement is a human being conditioned to some state of mind. The results show that the wireless EEG signal detection system using Bluetooth transmission has been able to transmit sensor data well, without delay and can connect automatically with Arduino. The detection results can be monitored directly on the GUI display of the LabView software and a graph of the frequency range can be seen.